Cadmium(II) coordination polymer based on flexible dithiolate-polyamine binary ligands system: Crystal structure, Hirshfeld surface analysis, antimicrobial, and DNA cleavage potential. (1st January 2022) - Bhattacharjee, Tirtha; Adhikari, Suman; Datta, Abhijit; Daniliuc, Constantin-Gabriel; Montazerozohori, M.; Naghiha, R.; Hayati, P.
Graphical abstract: Highlights: The mononuclear chelating complex [Cd(i-mnt)(tren)]n (1) fabricated from 1, 1-dicyanoethylene-2, 2-dithiolate ( i-mnt −2 ) and diethylenetriamine ( tren ) has been synthesized and structurally characterized. Single crystal X-ray diffraction analysis revealed that in 1, Cd +2 has CdN3 S3 coordination kernel having distorted trigonal prism geometry (TP) [twist angle (θ) 37.6(11) 0 ]. The Hirshfeld surface analysis corroborates well with X-ray data and explores all possible intermolecular interactions especially dominant N···H (16.6%) and H···S (7.3%) contacts. The MIC, MBC and in-vitro antibacterial study against Gram-positive ( Staphylococcus aureus, Bacillus subtilis ) and Gram-negative ( Escherichia coli, Pseudomonas aeruginosa ) human pathogenic bacterial strains shows promising bactericidal activity. Cd(II) complex is found to have potential in-vitro antifungal activity against Aspergillus niger and Candida albicans, along with promising DNA cleaving property due to the competent coordination of Cd +2 ion. Abstract: The mononuclear chelating complex [Cd(i-mnt)(tren)]n (1) fabricated from binary ligand systems 1, 1-dicyanoethylene-2, 2-dithiolate ( i-mnt −2 ) and diethylenetriamine ( tren ) has been synthesized and structurally characterized by spectroscopic methods (IR, NMR). The single-crystal X-ray diffraction study reveals that Cd +2 has CdN3 S3 coordination kernel having distorted trigonal prism geometry (TP) [twist angle (θ) 37.6(11) 0 ] and the secondary ligand tren influences the ligation pattern of i-mnt −2 towards metal center in the formation of 1D polymeric chain where asymmetric units linked by bridging thiolate S2-atom of each i-mnt −2 . The N H···N, N H···S type hydrogen bonds link the 1D polymeric chains in a 3D stacked chain supramolecular arrangement with apparent graph-set-motifs R 1 1 8, C(4), and C(8). The Hirshfeld surface analysis corroborates well with X-ray data and explores all possible intermolecular interactions especially dominant N···H (16.6%) and H···S (7.3%) contacts. The MIC, MBC and in-vitro antibacterial study against Gram-positive ( Staphylococcus aureus, Bacillus subtilis ) and Gram-negative ( Escherichia coli, Pseudomonas aeruginosa ) human pathogenic bacterial strains shows promising bactericidal activity. In-vitro antifungal study disclosing more activity against Aspergillus niger compared to Candida albicans at 50 mg/mL. DNA cleavage study ( E. coli DNA) via Agarose gel electrophoresis shows DNA cleaving property of the title compound similar to that of H2 O2 due to the suitable coordination of Cd(II) metal center.